Zasada pogłębiania zaufania obywateli do administracji publicznej jako fundament postępowania administracyjnego - Smarż, Joanna (PRAWO i WIĘŹ, 2025)
The principle of increasing confidence is considered by both doctrine and case law as a legal norm applicable to the entire field of administrative law. It is particularly important in the relationship between the administrative body and the individual (as the subject of administration) in the application of substantive law, i.e. in administrative proceedings. Uniformity and predictability of decisions are also important for building trust in public administration. This principle was explicitly articulated in the newly added § 2 of Article 8 of the Code of Administrative Procedure as part of the major amendment of the Code in 2017. As rightly recognised by the legislator, unjustified changes in the administrative authority's position undermine the confidence of the parties to proceedings in the public authority.